Competition and Bank Opacity - Jiang, Liangliang; Levine, Ross; Lin, Chen (Review of Financial Studies, 2016)
Did regulatory reforms that lowered barriers to competition increase or decrease the quality of information that banks disclose to the public? By integrating the gravity model of investment with the state-specific process of bank deregulation that occurred in the United States from the 1980s through the 1990s, we develop a bank-specific, time-varying measure of deregulation-induced competition. We find that an intensification of competition reduced abnormal accruals of loan loss provisions and the frequency with which banks restate financial statements. The results suggest that competition reduces bank opacity, potentially enhancing the ability of markets to monitor banks. Received July 7, 2015; accepted February 4, 2016 by Editor Philip Strahan.